Results of Surgical Management of Highly Unstable Complex Distal Femur Fractures with Distal Femoral Locking Compression Plate Fixation: A Prospective Study of 58 Cases (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: DF-LCP; lateral approach; schatzker and lambert criteria; secondary arthritis